Foreign and security policy decisionmaking under Yeltsin - Larrabee, F. Stephen; Karasik, Theodore William; Rand eBooks (Santa Monica, CA : RAND, 1997)
Five years after the collapse of the Soviet Union, Russian national security decisionmaking--and Russian security policy in general--remains in a state of flux. Despite several attempts, Russian President Yeltsin has failed to set up an effective system to coordinate and integrate national security policy. This report traces the bureaucratic struggle for control of Russian foreign and security policy during Yeltsin's tenure. It shows how special interest groups and bureaucratic actors have often been able to dictate policy without clear overall guidance. Since late 1995, Yeltsin has taken a number of steps designed to address these weaknesses and give foreign and security policy greater consistency and coherence, including replacing a number of key figures in the government. However, these moves have not resolved many of the basic problems. The report suggests strategies for managing U.S.-Russian relations in light of the current highly fluid situation within the top echelons of the Yeltsin government and the uncertainties surrounding Yeltsin's health.
"National Defense Research Institute."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: National security -- Russia (Federation); Russia (Federation) -- Foreign relations -- United States; Russia (Federation) -- Foreign relations; United States -- Foreign relations -- Russia (Federation); Electronic books